Protective Role for LPA3 in Cardiac Hypertrophy Induced by Myocardial Infarction but Not by Isoproterenol - Cai, Lin; Fan, Guangpu; Wang, Fang; Liu, Si; Li, Tiewei; Cong, Xiangfeng; Chun, Jerold; Chen, Xi (Frontiers in Physiology, 2017)
Background: We previously reported that lysophosphatidic acid (LPA) promoted cardiomyocyte hypertrophy in vitro via one of its G protein-coupled receptor subtypes, LPA3. In this study, we examined the role of LPA3 in cardiac hypertrophy induced by isoproterenol (ISO) and myocardial infarction. Methods: In vitro, neonatal rat cardiomyocytes (NRCMs) were subjected to LPA3 knocked-down or pretreated with a β-adrenergic receptor (β-AR) antagonist (propranolol) before LPA/ISO treatment. Cardiomyocyte size and hypertrophic gene (ANP, BNP) mRNA levels were determined. In vivo, LPA3-/- and wild-type mice were implanted subcutaneously with an osmotic mini-pump containing ISO or vehicle for 2 weeks; echocardiography was performed to determine the heart weight/body weight ratio, cardiomyocyte cross-sectional area, and level of ANP mRNA expression. LPA3-/- and wild-type mice were subjected to permanent coronary artery ligation or sham surgery for 4 weeks; cardiac function, including the degree of hypertrophy and infarction size, was determined. Results: In vitro, we found that knocked-down LPA3 in NRCMs did not attenuate ISO-induced hypertrophy, and propranolol was unable to abolish LPA-induced hypertrophy. In vivo, chronic ISO infusion caused cardiac hypertrophy in wild-type mice, while hypertrophic responses to ISO infusion were not attenuated in LPA3-/- mice. However, in a myocardial infarction (MI) model, LPA3-/- mice exhibited reduced cardiac hypertrophy compared to wild-type mice at 4 weeks post-MI, which was associated with reduced cardiac function and increased infarct size. Conclusions: Our data show that LPA3 appears to play a protective role in myocardial hypertrophy post-MI, but does not appear to be involved in the hypertrophy that occurs in response to β-AR stimulation in vivo and in vitro. These results implicate LPA-LPA3 lipid signaling in cardiac hypertrophy occurring after pathological insults like MI, which presents a new variable in β-AR-independent hypertrophy. Thus, modulation of LPA3 signaling might represent a new strategy for preventing the stressed myocardium from ischemia injury.